PENGATURAN REHABILITASI BAGI NOTARIS YANG DINYATAKAN PAILIT MENURUT UNDANG UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN HUTANG - hernawan aziz nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purposes of this study are to analyze and examine the rehabilitation arrangements for Notaries declared bankrupt according to Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations; and the legal consequences of temporary dismissal of Notaries that exceed the time period according to Law Number 2 of 2014 Position. This research uses normative legal research with statutory and conceptual approaches and qualitative analysis as data analysis. The results of the research are first, rehabilitation applied to Notary should be able to restore his position so that this is fairly applied to all bankrupt debtors without exception. The separation between the position and Notary as a person should be considered for the reappointment for Notary by the Minister. It should be emphasized that the focus of bankruptcy is the debtor's assets, not his/her person, so that the Notary's position should be restored; second a Notary temporarily dismissed in a bankruptcy process that exceeds the 6 (six) month time limit will result in the uncertain status of the Notary position and substitute Notary also automatically ends when the temporary dismissal date ends, and the protocol must be returned to the Notary concerned. There is no regulation regarding the extension of the temporary dismissal period of a Notary due to bankruptcy proceedings which implicate the principle of business continuity that is not fulfilled and the principle of legal certainty regarding the status of the Notary position